Pengembangan Media Pembelajaran Interaktif Berbasis Nearpod pada Tema Sungguh Kayanya Negeriku Subtema Pemanfaatan Kekayaan Alam di Indonesia - Rahmawati, Henny Annisa; Anwar, Wawan S; Mirawati, Mira (Jurnal PGSD, 2023)
The purpose of this study was to develop and determine the feasibility interactive learning media  using Nearpod application on the theme of my country's rich sub-theme of utilizing natural wealth in Indonesia in elementary schools. This research is a development research with a modified ADDIE development model. This development model consists of analysis, design, development, implementation and evaluation. The results of media expert validation showed a percentage of 97.33% with the category "Valid", the results of validation of linguists showed a percentage of 94.66% with the category "Valid" and the results of material expert validation showed a percentage of 98.66% with the category "Valid". The nearpod media is then tested on grade IV students to see the responses of teachers and learners. The teacher's response results were obtained by a percentage of 95% and the response results of students received a percentage of 89% with the criterion of "Very Good". It was concluded that the development of nearpod-based interactive learning media on the theme of my country's rich sub-theme of utilizing natural wealth in Indonesia is worthy to use for learning in class IV.